THE EFFECT OF USING THE ABC-EOQ-ROP METHOD ON THE FREQUENCY OF DRUG EMPTINESS IN THE HOSPITAL - Burhan, M.; Winarsih, Sri; Harijanto, Tatong (Universitas Brawijaya, Indonesia, 2019)
This study aims to determine the effect of the use of inventory control methods of always better control (ABC), economic order quantity (EOQ), and reorder point (ROP) supported by a computer-based daily stock information system of drugs and consumable medical devices on the emptiness of drugsfrequency and vital types of medical devices use at the Bangil Hospital Pharmacy Installation.This type of quantitative research uses a preexperimental design with one group pre and post-test design. Data analysis using t-test and normality test with the Kolmogorov-Smirnov Test. The sample data used were emptiness drugs and vital consumables, with observations of vacancy data from May 2016 to May 2017, nine months before the intervention and three months after the intervention, the effects were analyzed using the t-test.The results show that there is a significant influence on the use of inventory control methods to reduce the frequency of emptiness of drugs and vital types of consumables. If there are emptiness drugs, make other efforts in fulfilling drug procurement.